2e Atelier nitrate-eau Evaluation du Programme de gestion durable de l'azote. 28 mai-1er juin 2012, Peyresq, France - Vandenberghe, Christophe; Destain, Jean-Pierre; Marcoen, Jean Marie; Colinet, Gilles (Uliège Library, 2013)
As part of this evaluation mission, GRENeRA organized the first Nitrate-Water Workshop in 2009. The proceedings of this workshop were published in a special issue of the journal BASE. GRENeRA organized, from May 27 to June 1, 2012, the second Workshop which gathered about fifteen scientists from Wallonia (Université Catholique de Louvain, Centre wallon de Recherches Agronomiques, Services Agricoles de la Province de Liège, Université de Liège and ULg - Gembloux Agro-Bio Tech) and France (INRA, Agrocampus Rennes). The workshop was devoted successively to the study of the following four themes - water (evolution of water quality and eutrophication, agronomic experiments on a point, plot or watershed scale with impact measurements on water) - grassland (grazing management, fertilization) and livestock (balance of feed rations and nitrogen production by animal category) - crops (including crop succession and intercropping) and fertilizers (organic and mineral nitrogen management), - recommendations for the revision of the PGDA, scientific research, supervision and communication. Compared to 2009, the recommendations have been enriched with thoughts on eutrophication and have taken into account the potential impact on the environmental issues of "plant protection products" and "greenhouse gases" in order to avoid losing with one hand what we have been able to gain with the other. The following articles illustrate the work of the scientists presented and discussed during this 2nd Nitrate-Water Workshop.